Leveraging bifunctional phosphide-based catalysts in a membrane-electrode-assembly to achieve industrial hydrogen production - Zeng, Wen-Jing; Ma, Jian-Jie; Huang, Wen-Yang; Lee, Tsung-Ju; Lin, Zih-Yi; Peng, Kang-Shun; Hiraoka, Nozomu; Liao, Yen-Fa; Lu, Ying-Rui; Hu, Chih-Wei; Hsu, Shao-Hui; Hung, Sung-Fu (Materials Today Sustainability, 2024)
The advancement of the hydrogen economy hinges upon the development of clean, cost-effective, and highly efficient hydrogen generators capable of industrial-scale operation. Conventional electrolyzers encounter challenges such as high internal resistance and low current density, which restrict their practical applicability. In this study, we present a cost-effective bifunctional CoFeP electrocatalyst wherein the regulation of cobalt 3d orbitals by iron dopants enhances overall catalytic activity. High-energy-resolution fluorescence-detection X-ray absorption spectroscopy and 1s3p resonant inelastic X-ray scattering confirm a downward shift and delocalization of cobalt ion 3d orbitals. Employed within a membrane-electrode assembly (MEA) system, CoFeP demonstrates voltages of 1.51 V at 10 mA cm−2, 1.65 V at 100 mA cm−2 and 2.11 V at 500 mA cm−2 without iR-correction. These values are significantly lower by 109 mV and 470 mV than those recorded at 100 mA cm−2 (1.62 V) and 500 mA cm−2 (2.71 V), respectively, in a conventional H-cell system. Within the MEA system, CoFeP achieves a Faradaic efficiency exceeding 97% for hydrogen production and sustains stable catalytic for 350 h, underscoring its potential for industrial-scale hydrogen production. A low-cost bifunctional CoFeP electrocatalyst in a membrane-electrode assembly (MEA) system was demonstrated, showing significant higher catalytic current density than the conventional system. [Display omitted]